Influence of the graphene oxide on heat conduction characteristics of cement-based honeycomb scaffolds - Zhangjianing Cheng; Yuan Gao; Youjian Zhang; Sijia Wang; Xinlei Mao; Lei Feng; Qiuchen Liu; Yanming Liu (Case Studies in Construction Materials)
Cement-based honeycomb scaffolds, characterized by their superior plastic deformation, lightweight, high specific stiffness, and thermal insulation, offer promising improvements in the quality and stability of external wall materials. It has been reported that graphene oxide (GO) can substantially increase the compressive strength of these structures. Although GO is known for its outstanding thermal conductivity, its impact on the heat conduction characteristics of cement-based honeycomb scaffolds remains to be fully understood. In this study, the influence of GO on the temperature field evolution and heat conduction in cement-based honeycomb scaffolds was examined. The findings suggest that as GO concentration increases, the thermal insulation capacity of the scaffolds initially improves but then declines. At a GO concentration of 0.5 wt%, the thermal insulation performance is optimal, reducing the temperature by 1–5°C and shortening the heat conduction time to stabilization by 40 % compared to pure cement. The incorporation of GO induces nucleation and pore-infilling effects, strengthening the pore structure of the coated cement and complicating the heat conduction pathway, ultimately reducing heat transfer in cement-based honeycomb scaffolds. These findings help the understanding of GO's impact on the thermal properties of cement-based honeycomb scaffolds and highlight the potential application of GO-reinforced cementitious honeycomb materials in lightweight, thermally insulating, low-carbon, and energy-efficient construction.